The Islamic rooting of causes and methods managing organizational conflict - Aldaadi, Dalal Dabes Mohammed (Journal of Educational and Psychological Sciences, 2023)
This study aimed at the Islamic rooting of causes and methods managing organizational conflict according to Islamic faith. The study used the archival study. The study concluded that there are many causes of organizational conflict such as limited resource, lack of clarity of powers, and reasons related to personal relationships such as misinterpretations. Also, there are several methods for managing conflict, the most important of which is arbitration, mediation, refer to expertise, and negotiation. Finally, the study recommended the need to pay attention to the rooting of various educational management topics to create a database based on the foundation of the Islamic religion, the need to direct scientific research in the field of administrative sciences to serve the Islamic world, and to encourage postgraduate students to root the issues of educational administration.